Radio Frequency Identification (RFID) Adoption in Healthcare Linen Management: A Case study at ProLinenCare (Global Business Management Review (GBMR), 2018)
The Malaysian healthcare industry is experiencing a steady growth, rapidly expanding to meet the needs of society. Expectedly, this development led to a high demand for healthcare linen. With increasing competition, healthcare linen and laundry services (LLS) provider companies need to efficiently cope with the impending demand and business issues / challenges. Presently, ProLinenCare, a fast growing linen and laundry company in Malaysia is struggling with healthcare linen management which gives a strong impact on its total inventory management. The company’s Linen Manager, Mrs. Sharon is looking for an immediate solution to increase efficiency in healthcare linen management in order to meet the customers’ demand. Thus, a comprehensive study is essential and need to be carried out systematically in order to identify the possible solution(s). The company should take various factors into account, including technological advancements. Radio Frequency Identification (RFID) technology is a fast growing technology that is able to produce major changes in healthcare linen management. The primary purpose of this paper is to demonstrate the ways to increase efficiency in healthcare linen management by adopting RFID technology. A case study was initiated at ProLinenCare (M) Sdn Bhd. The case study was carried out by assessing the key processes in healthcare linen management, interviewing key personnel and reviewing selected secondary data. In addition, an observation of data obtained from the laundry site visits was also conducted to evaluate the business issues / challenges and suggest mitigation plan to increase efficiency in healthcare linen management in order to meet performance indicators and exceeding customer satisfaction.